Theoretical Calculations For Sputtering Yield of Nickel Surface Hitted By Xenon Plasma Ions - Younis, Duraid H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Extended calculations for sputtering yield through bombed Nickel – target by Xenon ions plasma are accomplished. The calculations include changing the input parameters: the energy of xenon ions plasma, the hit target angle of nickel target, thickness of the nickel target layer, and the slight change in the surface binding energy of Nickel. The program TRIM is used to accomplish these calculations. The results show that the sputtering yields directly dependent on these parameters. The change in angles of incidence plasma ions and energy leads to a significant change in the sputtering yields. On the other hand, the sputtering yields ore highly affected by changing target width and surface binding energy at fixed ion parameters.